Efficient transactivation by retinoic acid receptors in yeast requires retinoid X receptors. - Heery, D M (1993)
All-trans and 9-cis retinoic acids are natural derivatives of vitamin A that modulate gene expression as a consequence of binding to nuclear retinoic acid receptors (RARs) and retinoid X receptors (RXRs). RXRs form heterodimers with RARs in vitro, and such complexes display enhanced binding affinities for cognate DNA response elements. As yeast is devoid of endogenous RARs and RXRs, we used this organism to investigate whether transactivation in vivo requires RAR/RXR heterodimers. Using a domain-swapping approach, we demonstrate that chimeric RAR alpha 1 and RXR alpha containing the DNA-binding domain of the estrogen receptor activate transcription of a cognate reporter gene in yeast, independently of each other. These activities result from an inducible transcription activation function located in the ligand-binding domains of RAR alpha 1 and RXR alpha and a constitutive activation function located in the A/B region of RAR alpha 1. The inducible activation function of RXR alpha is induced exclusively by 9-cis-retinoic acid in this system. Transactivation of a reporter gene containing a retinoic acid response element by RAR alpha was considerably increased by RXR alpha, even in the absence of ligand. Optimal induction was achieved with 9-cis-retinoic acid, which stimulates the activity of both receptors. This study illustrates the utility of yeast to investigate signal transduction by retinoids in the absence of endogenous RARs, RXRs, and detectable retinoic acid isomerization.